2009
DOI: 10.1590/s1980-57642009dn30200009
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension and storage of sequentially presented radio news items by healthy elderly

Abstract: In the normal aging processes, complaints of memory loss and auditory comprehension are not uncommon, principally in complex and cognitively demanding situations.ObjectiveThe objective of this study was to investigate skills of discourse comprehension and retention in a natural situation, by healthy aged in relation to variables such as age, schooling and cognitive screening measurement.MethodsThirty healthy elderly participated in the study (mean age=73.56 yrs; SD=6.26 and mean schooling=8.6 yrs; SD=4.41). Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Difficulties related to the coordination of concurrent processes in complex linguistic activities, temporary information storage and oversight of these activities have been mentioned as determinants in misunderstandings. 2,27 Other studies show significant association between oral speech comprehension outcome with sociodemographic variables: age, educational level and literacy; with the variables of health conditions: hypertension diagnosis, cognitive and mental state; and social relations in self-assessment of comprehension in conversations. 7,28,29 Data from this study revealed a prevalence of 10.69% of self-reported difficulty in oral comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties related to the coordination of concurrent processes in complex linguistic activities, temporary information storage and oversight of these activities have been mentioned as determinants in misunderstandings. 2,27 Other studies show significant association between oral speech comprehension outcome with sociodemographic variables: age, educational level and literacy; with the variables of health conditions: hypertension diagnosis, cognitive and mental state; and social relations in self-assessment of comprehension in conversations. 7,28,29 Data from this study revealed a prevalence of 10.69% of self-reported difficulty in oral comprehension.…”
Section: Discussionmentioning
confidence: 99%